Customer loyalty on sharia banking: the effect of brand image and customer value / Julina Julina and Fakhrurrozi Fakhrurrozi - Julina Julina; Fakhrurrozi Fakhrurrozi (UiTM Cawangan Johor, 2020)
This study aims to determine the effect of brand image on customer loyalty both directly and through customer value on sharia banking operated in the city of Pekanbaru. Data collection was done by using a questionnaire distributed to sharia bank customers in Pekanbaru, Indonesia. The data that have been collected were tested for validity and reliability, and then to find out the relationship between the variables the data were processed using structural equation modeling. The results found that brand image and customer value have a positive and significant effect on customer loyalty. In addition, the brand image also has a positive and significant effect on customer value. The direct effect of brand image on customer loyalty is smaller than the indirect effect of brand image on customer loyalty through customer value. Based on the calculations, it is evident that customer value is a partial mediation for the influence of brand image on customer loyalty. The results of this study state that in order to maintain customer loyalty, sharia banking must continue to strengthen the brand image and customer value that have become their hallmark and mainstay to win the competition.